Legal framework for waqf of immoveable property in Malaysia - Syed Abdul Kader, Sharifah Zubaidah; Mohamad, Nor Asiah (Universiti Tun Abdul Razak Sdn Bhd in collaboration with International Centre for Waqf Research (ICWR) of International Islamic University Malaysia (IIUM), Malaysia, 2017)
This paper explores issues arising in the administration and management of waqf lands in Malaysia in relation to the existing legal framework. Focusing on the management of waqf lands where the waqif creates waqf under Islamic law, this paper posits that in Malaysia, the concept of waqf is different from the concept of trust as each falls under different laws and governance structures and there may be certain legal implications where the two are taken to be the same. After examining the various ways in which waqf lands are vested on the State Islamic Religious Councils (‘SIRCs’) under land law, this paper notes that there is an impasse in efforts to standardise methods of vesting waqf lands in the name of the respective SIRCs. The writers take the stand that although the creation and validity of waqf should go beyond the land law requirements, it is this requirement that stands as formal recognition of waqf lands by government agencies and the courts. Many issues arise due to incomplete information or evidence to prove that waqf has been created over a piece of land. In this regard, the general land laws prevail in the absence of specific provisions or evidence proving otherwise. Thus, confusion in management may arise that necessitates cooperation of all affected agencies. These challenges and hindrances are further examined in this paper with suggestions for improvements.